2017
DOI: 10.1016/j.ajme.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and epidemiological features of cutaneous leishmaniasis in southwest of Iran

Abstract: Introduction: Leishmaniasis, as a major health concern exists in 14 out of 22 countries of the Eastern Mediterranean Region (EMR). Therefore, the aim of present investigation was to evaluate the epidemiological features and spatial distribution of cutaneous leishmaniasis (CL) during six consecutive years (2009-2014). Material and methods: In current retrospective cross-sectional study among 2009-2014, simple direct smear was taken from all suspicious CL subjects who referred to health centers affiliated to Ahv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…Retrospective studies play a significant role in this process, since trends can be identified, and then prevention and control measures can be formulated. Of note, studies in Brazil and Iran have evaluated the spatial distribution and epidemiological characteristics of leishmaniasis, becoming the starting point for a more effective allocation of resources, guiding national and regional public health policy [ 41 , 42 ]. Despite the existence of a reporting system, underreporting is common in the most remote rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies play a significant role in this process, since trends can be identified, and then prevention and control measures can be formulated. Of note, studies in Brazil and Iran have evaluated the spatial distribution and epidemiological characteristics of leishmaniasis, becoming the starting point for a more effective allocation of resources, guiding national and regional public health policy [ 41 , 42 ]. Despite the existence of a reporting system, underreporting is common in the most remote rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Khuzestan province is one of the endemic areas of cutaneous leishmaniasis in Iran, with the dominance of L. major (3). In this study, all samples were diagnosed as positive by the direct microscopic examination and the parasite species were determined to be L. major by Nested PCR.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, Khuzestan province is one of the main endemic areas for cutaneous leishmaniasis in Iran, which needs attention (3). Cutaneous leishmaniasis accounts for most cases of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease the CL incidence in Tunisia during future years, some points are recommended and should be considered such as health education and awareness about disease, traffic control of immigrants and travelers to endemic regions, personal protection from sandfly biting by curtains and bed nets, eliminating and destroying habitats of the reservoir rodent and spraying insecticides in habitats of sandflies [38]. Therefore, the high awareness among the community, health decision and policy makers were key elements for sustainability of surveillance and control measures in Tunisia.…”
Section: Consequently In 2000 the Tunisian National Control Of Paramentioning
confidence: 99%